Level of implementation of the IFRS in the funeral homes of Villavicencio – Colombia (GEON Journal (Management, Organizations and Business), 2018)
This article identifies and analyzes the level of implementation of international financial reporting standards IFRS in funeral SMEs of the city of Villavicencio. To achieve this purpose, a Systematic Literature Analysis was developed through a qualitative-quantitative approach study, supported by descriptive research, taken as a population to 6 funeral centers, SMEs, applying the information collection instrument to the area manager. accounting of the company. The findings allow to demonstrate the low degree of compliance with the regulations on the adoption of IFRS by funeral homes Villavicencio, although there is a good general perception of the international standard; Results with which recommendations were formulated that make possible the implementation of the NIFF in the population under study.
Keywords: IFRS; implementation; SMEs; Implementation NIIF